2017
DOI: 10.1080/09286586.2017.1367410
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physical Activity and Sedentary Behaviour with Vision-Threatening Diabetic Retinopathy in Indonesian Population with Type 2 Diabetes Mellitus: Jogjakarta Eye Diabetic Study in the Community (JOGED.COM)

Abstract: In this study, prolonged daily sedentary activity was strongly associated with VTDR. This finding suggests that public health campaign for reducing daily sedentary activities in individuals with type 2 diabetes may offer benefit to reduce the burden of DR and VTDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
2
17
2
2
Order By: Relevance
“…Some evidence suggests that AE may protect retinal cells from diabetes-induced injuries by inhibition of the underlying inflammatory and oxidative stress pathways (Dharmastuti et al, 2018). Loprinzi, Brodowicz, Sengupta, Solomon, and Ramulu (2014) In a cohort study in diabetic patients, Kuwata et al (2017) found that higher levels of AE are associated with a lower incidence of DR,…”
Section: Ae and Drmentioning
confidence: 99%
“…Some evidence suggests that AE may protect retinal cells from diabetes-induced injuries by inhibition of the underlying inflammatory and oxidative stress pathways (Dharmastuti et al, 2018). Loprinzi, Brodowicz, Sengupta, Solomon, and Ramulu (2014) In a cohort study in diabetic patients, Kuwata et al (2017) found that higher levels of AE are associated with a lower incidence of DR,…”
Section: Ae and Drmentioning
confidence: 99%
“…No associations were found in type 1 diabetes patients in the Pittsburgh study [ 4 ], and a protective effect of PA on DR risk was observed in women only in the WESDR study [ 5 ]. Studies conducted in type 2 diabetic patients found that higher levels of PA were associated with milder DR and less likelihood of DR onset; these studies were cross-sectional in design or limited by small sample size [ 6 8 ]. There is only one longitudinal study recently published, reporting a lower DR incidence in participants with higher PA levels, but this study was conducted in a small sample of the cohort during 2-year follow-up [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed study sampling and methodology have previously been described (23)(24)(25). Briefly, JOGED.COM (Jogjakarta Eye Diabetic Study in the Community) was a community-based cross-sectional study recruiting participants aged .30 years with type 2 diabetes confirmed by their family physician (using one of the following criteria: fasting plasma glucose $126 mg/dL, random glucose $200 mg/dL, or A1C $6.5%).…”
Section: Methodsmentioning
confidence: 99%